BIOGEOCHEMICAL ASPECTS OF THE GENESIS OF SALINE MARSHY SOILS - Yuldashev Gulom; Khakimjonova Nazokatkhon (Web of Journals Publishing, 2025)
The marshy soils formed in Central Fergana have been studied along with other hydromorphic soils. The research investigates the role of suspended sediments in soils under the influence of irrigation waters and water accumulation, as well as the partial role of ancient lake-alluvial deposits in soil genesis.
Keywords: Marshy, grassland, hydromorphic, oxidation, reduction, gleying, alluvial, peat, accumulation, regeneration.